Strategy For Increasing Market Retribution in The Regional Company Horas Jaya Marketing - Sriwiyanti, Eva; Sehat Sihite, Toga; Nainggolan, Pinondang; Manawari Girsang, Rosita; Sjafei Purba, Djuli; Munthe, Risma (KnE Social Sciences, 2023)
The research objective was to analyze the strategy to increase the market retribution of the Horas Jaya Regional Company in Pematangsiantar City. This research uses descriptive research. This type of data consists of primary data through interviews related to the research problem, as well as direct observation of the research object. Secondary data were obtained from existing documents at the Regional Company Pasar Horas Jaya Kota in Pematangsiantar. To analyze the data obtained, the authors used descriptive and qualitative data analysis methods. The results of this study are the existence of a strategic location and increased user fees and reduction of employees who are the prima donna of local revenue in Pematangsiantar city. It can be seen from the weight and rating in doing research for gain weight and rating 80% of the subsector levies has become a source of local revenue Pematangsiantar. Likewise with the planning carried out by the Horas Jaya Market Regional Company in Pematangsiantar City to increase the acceptance of market retribution in Pematangsiantar City, in terms of determining the maximum possible target, the targets are carried out according to market conditions and based on all types of potential that exist in the Horas market. In terms of the implementation of Human Resources (officials or officers) who carry out the collection has not been maximized and there are assets in the form of market land that have not been managed by the Horas Jaya Market because from the results of existing research: the target and the realization of market charges have never reached the target. Keywords: Market retribution; strategy; marketing